Pengaruh Pemberian Pupuk Organik Guano Terhadap Pertumbuhan dan Hasil Tanaman Sawi Hijau (Brassica juncea L.) - I Made Suryana; I Putu Sujana; Yohana Ratna Gai (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
According to BPS data, mustard greens increased by 667,473 tons/ha in 2021, and in 2022 to 3,324 tons/ha. The decrease caused by various kinds, one of which is a decrease in land quality. Therefore, research on dosing guano organic fertilizer on mustard greens needs to be carried out with the aim of: 1) knowing the effect of applying guano organic fertilizer on the growth and yield of mustard greens (Brassica juncea L.). 2) find out what dose of guano fertilizer is best for the growth and yield. This study used a Randomized Group Design with 6 treatments, namely G0: no guano fertilizer treatment, G1: 4 tons/ha , G2: 8 tons/ha, G3: 12 tons/ha, G4:16 tons/ha, G5: 20 tons/ha. Each treatment was repeated 4 times So that 24 treatment parameters were observed, namely plant height, number of leaves, leaf area, total fresh weight of the plant and fresh weight of the total oven dry plant. The results of this study showed that the effect of applying guano fertilizer dose treatment on mustard greens (Brassica juncea L.) had a very noticeable effect on plant height, leaf area, total plant fresh weight, total oven dry weight of the plant and had no real effect on the number of leaves. The application of guano fertilizer dose 480 g / 10 kg of soil gives the best results against the growth and yield of mustard plants with a maximum total fresh weight of 642.5 g, and a maximum total oven dry weight of 35.3 g.